Whole genome sequence and annotation dataset of rare actinobacteria, Barrientosiimonas humi gen. nov., sp. nov. 39T from Antarctica ... - Chong, Sin Yee; Azmi, Aida Azrina; Cheah, Yoke Kqueen (Zenodo, 2023)
The present data files are the source files of the annotation output from the whole genome sequencing of rare actinobacteria, Barrientosiimonas humi gen. nov., sp. nov. 39 T from Antarctica. The dataset of the whole-genome sequence of B. humi had been deposited in European Nucleotide Archive (ENA) repository under the accession number PRJEB44986 / ERP129097, direct URL to data: https://www.ebi.ac.uk/ena/browser/view/PRJEB44986 ... : {"references": ["European Nucleotide Archive. (2021). Project PRJEB44986: Whole-genome Sequencing and Annotation of Barrientosiimonas humi gen. nov., sp. nov. 39T, a Novel Rare Actinobacteria from Barrientos Island, Antarctica. ENA Browser. PRJEB44986. Retrieved from https://www.ebi.ac.uk/ena/browser/view/PRJEB44986"]} ...